Thriving in change: Examining the influence of organizational sustainability on employee performance in the post-COVID landscape - Junça Silva, A.; Costa, S. (International Journal of Organizational Analysis, 2026)
Purpose The economic, financial and social crisis has heightened researchers' interest in the importance of organizational sustainability and resources (e.g. work engagement and psychological capital) for performance. Despite some studies demonstrating the significance of resources, such as work engagement and psychological capital, for workers’ performance, there is limited knowledge regarding the role of organizational sustainability practices (OSP) in the relationship mentioned above. Therefore, this study drew upon the social identity theory to conceptualize and test the mediating role of work engagement in the relationship between OSP and performance (both task and adaptive). Based on the conservation of resources theory, it was hypothesized that a worker's resource – psychological capital – would moderate the indirect relationship between social responsibility practices and performance (both task and adaptive). Design/methodology/approach To test the proposed model, 304 adults participated in a two-wave study. Findings The results supported the hypotheses, revealing that OSP had a positive and significant relationship with task and adaptive performance, occurring through work engagement. Furthermore, the indirect relationship between OSP and performance task and adaptive through work engagement was moderated by psychological capital, such that the relationship became stronger for workers with lower levels of psychological capital. Originality/value The relevance of this research lies in its ability to identify the conditions and mechanisms in which corporate social responsibility initiatives are most effective, thereby enabling a more nuanced application of these practices across different sectors and organizational cultures. This study's theoretical and practical implications may assist organizations in devising strategies for implementing social responsibility practices to enhance their outcomes.